1990
DOI: 10.3109/02699059009026191
|View full text |Cite
|
Sign up to set email alerts
|

Long-term multi-dimensional outcome following isolated traumatic brain injuries and traumatic brain injuries associated with multiple trauma

Abstract: We retrospectively investigated long-term, multi-dimensional quality-of-life outcomes in 68 male patients who suffered pure head injuries and 63 male head-injured patients with associated multiple trauma. Results indicated that patients sustaining associated multiple trauma were significantly younger and more deeply comatose on admission. Trends were found to suggest that patients sustaining associated multiple trauma also remain in coma longer, and experience more difficulties in social interaction and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although there is no prospective study that compares the outcome of polytraumatized patients with and without TBI, there is evidence of a negative influence of TBI itself and the effects of systemic alterations common in polytraumatized patients on the time course of acute brain injury [7,13,14,17,21,22,28,45). Therefore, the issue of this review is to point out these predictive and sometimes avoidable factors from the pathophysiological and clinical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no prospective study that compares the outcome of polytraumatized patients with and without TBI, there is evidence of a negative influence of TBI itself and the effects of systemic alterations common in polytraumatized patients on the time course of acute brain injury [7,13,14,17,21,22,28,45). Therefore, the issue of this review is to point out these predictive and sometimes avoidable factors from the pathophysiological and clinical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…TBI patients with multiple trauma have been found to have a longer duration in coma. In addition, they have greater problems with long-term psychosocial functioning, memory, attention and learning [57,58]. A study of 95 pediatric patients found that even though severity of head injury was greater in the isolated TBI patients, the TBI plus multiple trauma group had a twoand-a-half times greater frequency of poor outcome [59].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The third variable said to be predictive of severity of injury and outcome is the duration of PTA (Jennett & Teasdale, 1976). Moore, Stambrook, Peters, Cardoso, and Kassum (1990) classified PTA as the number of days that the GCS score remained below 15. Duration of PTA has been found to be related to the degree of disability, and when it persists for more than three weeks intellectual disability ensues to some degree (Jennett et al, 1976).…”
Section: Duration Of Post T R a U M A T I C Amnesiamentioning
confidence: 99%